SUPERVISI PENGAJARAN DENGAN PENDEKATAN DIREKTIF, NON-DIREKTIF, DAN KOLABORATIF - Afrijawidiya Afrijawidiya; Zakaria Zakaria; Osa Juarsa (UNIVERSITAS BENGKULU, 2017)
The purpose of this study is generally to describe the implementation of supervision approach teaching with the directive, non-directive, and collaborative carried principals to teachers in Public Junior High School Number 13 Lubuklinggau. This study uses descriptive qualitative research. The research subjects were the source of reference data, the principal, vice curriculum, and teachers. The data collection technique used is through interview, observation and documentation. Step analysis of data through data reduction, data presentation, and conclusion or verification.